Introduction to cyberbullying (Module 2). - MC GUCKIN, CONOR (Verlag Emprische Padagogik., 2013)
? Since the birth of the Internet a new form of bullying behaviour has emerged. Bullying has converged with the cyber world, producing the phenomenon we now call cyberbullying; ? Cyberbullying can be classified in two ways: by the channel through which the abuse occurs and by the nature of the abuse itself; ? Tactics used by cyberbullies to victimize their targets include bashing, harassment, denigration, exclusion, impersonation, flaming, trickery, outing, cyber stalking, and posing; ? It is thought that around 10% of children are involved in cyberbullying. This is based on European studies to date; ? Victims of cyberbullying express negative feelings such as rage and frustration with 10% of victims stating that they felt stressed by their experiences. Cyberbullying has also been linked to low self-esteem, loneliness, depression, difficulties with school functioning and in some cases has been a contributing factor in incidents of adolescent suicide.
New media and cyberbullying: An online course for parents.
PUBLISHED
Keywords: Bullying; Cyberbullying